MR fingerprinting as a diagnostic tool in patients with frontotemporal lobe degeneration: A pilot study. (8th August 2019) - Keil, Vera Catharina; Bakoeva, Stilyana Peteva; Jurcoane, Alina; Doneva, Mariya; Amthor, Thomas; Koken, Peter; Mädler, Burkhard; Block, Wolfgang; Fimmers, Rolf; Fliessbach, Klaus; Hattingen, Elke
Abstract : Several very rare forms of dementia are associated with characteristic focal atrophy predominantly of the frontal and/or temporal lobes and currently lack imaging solutions to monitor disease. Magnetic resonance fingerprinting (MRF) is a recently developed technique providing quantitative relaxivity maps and images with various tissue contrasts out of a single sequence acquisition. This pilot study explores the utility of MRF‐based T1 and T2 mapping to discover focal differences in relaxation times between patients with frontotemporal lobe degenerative dementia and healthy controls. 8 patients and 30 healthy controls underwent a 3 T MRI including an axial 2D spoiled gradient echo MRF sequence. T1 and T2 relaxation maps were generated based on an extended phase graphs algorithm‐founded dictionary involving inner product pattern matching. A region of interest (ROI)‐based analysis of T1 and T2 relaxation times was performed with FSL and ITK‐SNAP. Depending on the brain region analyzed, T1 relaxation times were up to 10.28% longer in patients than in controls reaching significant differences in cortical gray matter ( P = .047) and global white matter ( P = .023) as well as in both hippocampi ( P = .001 left; P = .027 right). T2 relaxation times were similarly longer in the hippocampus by up to 19.18% in patients compared with controls. The clinically most affected patient had the most control‐deviant relaxation times. There was a strong correlation of T1 relaxation time in the amygdala with duration of the clinically manifest disease (Spearman Rho = .94; P = .001) and of T1 relaxation times in the left hippocampus with disease severity (Rho = .90, P = .002). In conclusion, MRF‐based relaxometry is a promising and time‐saving new MRI tool to study focal cerebral alterations and identify patients with frontotemporal lobe degeneration. To validate the results of this pilot study, MRF is worth further exploration as a diagnostic tool in neurodegenerative diseases. Abstract : Magnetic resonance fingerprinting (MRF) can support diagnostic imaging in neurodegeneration by providing quantitative T1 and T2 relaxometric maps that differentiate frontotemporal dementia (FTD) spectrum patients from controls. Patients showed prolonged T1 relaxation time in gray and white matter and prolonged T1 and T2 relaxation in hippocampi compared controls. Relaxation times were variable between FTD subtypes in this pilot study, which needs clarification in larger trials.